Hollow multi-shell Co-N-C HoMS catalyst and method and application thereof
By developing a hollow multi-shell Co-N@CHoMS catalyst, the unique structure of its porous carbon shell and Co-N inner shell is solved, and the problem of difficult separation of natural organic matter and target pollutants in the prior art is achieved, and selective degradation and efficient catalysis of multi-component pollutants are achieved.
Patent Information
- Application Number
- CN202510122215.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-18
AI Technical Summary
Existing water treatment technologies are difficult to effectively separate natural organic matter and target pollutants, resulting in insufficiency of catalytic efficiency.
A hollow multi-shell Co-N@CHoMS catalyst is developed, which consists of a porous carbon shell and a Co-N inner shell that blocks the entry of macromolecules, and the Co-N inner shell is rich in active sites and is used to catalyze the activation of peroxy monosulfate and generate reactive oxygen species to degrade organic pollutants.
This catalyst can effectively separate natural organic matter and target pollutants, achieve selective degradation of multi-component pollutants, excellent catalytic performance, good stability, and simple preparation method.
Smart Images

Figure CN119633874A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental organic pollution remediation, and specifically relates to a hollow multi-shell Co-N@CHoMS catalyst and a preparation method thereof and an application in water treatment. Background Art
[0002] With the development of industry and agriculture, the types and quantities of organic pollutants in water bodies are increasing, posing a serious threat to human health and the ecological environment. Traditional water treatment technologies such as adsorption and biodegradation have problems such as low efficiency and poor selectivity. Peroxymonosulfate (PMS) is an efficient oxidant, and the reactive oxygen species (ROS) produced by its activation can effectively degrade organic pollutants. However, in natural water bodies, natural organic matter (such as humic acid) will occupy the active sites of the catalyst and reduce the catalytic efficiency. Therefore, it is of great significance to develop a catalyst that can effectively separate natural organic matter and target pollutants. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the prior art and provide a hollow multi-shell Co-N@CHoMS catalyst and method and application. The catalyst can effectively separate natural organic matter and target pollutants and achieve selective degradation of multi-component pollutants.
[0004] The specific technical solutions adopted by the present invention are as follows:
[0005] In the first aspect, the present invention provides a hollow multi-shell Co-N@C HoMS catalyst, comprising a porous carbon outer shell and a Co-N inner shell; the porous carbon outer shell is a porous structure for blocking large molecules from entering the interior; the Co-N inner shell is rich in active sites for catalyzing the activation of peroxymonosulfate to generate active oxygen species for degrading organic pollutants.
[0006] Preferably, the pore size of the porous carbon shell is 2-5 nanometers.
[0007] Preferably, the thickness of the Co-N inner shell is 1-3 nanometers.
[0008] Preferably, the catalyst has a specific surface area of 300-500 m2 / g and a pore volume of 0.5-1.0 cm3 / g.
[0009] In a second aspect, the present invention provides a method for preparing a hollow multi-shell Co-N@C HoMS catalyst, which is as follows:
[0010] S1, mixing ZIF-67 precursor with polydopamine to form ZIF-67@PDA complex;
[0011] S2. The ZIF-67@PDA complex was heated from room temperature to 425°C at a heating rate of 0.6°C / min under a nitrogen atmosphere, kept warm for 1 hour, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain a hollow multi-shell Co-N@CHoMS catalyst.
[0012] Preferably, in S1, the mixing mass ratio of ZIF-67 precursor to polydopamine is 1:(0.3-0.5).
[0013] Preferably, the preparation method of the ZIF-67 precursor is as follows:
[0014] 7.50 mmol of Co(NO 3 ) 2 6H 2 O and 32.3 mmol of 2-methylimidazole were dissolved in methanol and ethanol, respectively, mixed and allowed to stand at room temperature for sufficient reaction to obtain a ZIF-67 precursor.
[0015] In a third aspect, the present invention provides a method for degrading organic pollutants in water, as follows:
[0016] In the presence of peroxymonosulfate, the hollow multi-shell Co-N@C HoMS catalyst obtained by the preparation method according to any one of claims 1 to 4 or any one of claims 5 to 7 is added to a water body, so that the porous carbon shell of the hollow multi-shell Co-N@C HoMS catalyst blocks the macromolecules in the water body from entering the interior, and the active sites of the Co-N inner shell catalyze the activation of peroxymonosulfate, and the generated active oxygen species fully contact with the small molecular organic pollutants in the water body to achieve the degradation of the small molecular organic pollutants.
[0017] Preferably, the organic pollutants include carbamazepine, bisphenol A, phenol and p-chloroaniline, and the water body includes domestic sewage, industrial wastewater and surface water.
[0018] Preferably, the amount of the catalyst is 0.1-0.2 g / L, and the amount of peroxymonosulfate is 0.1-0.3 g / L.
[0019] Compared with the prior art, the catalyst of the present invention has the following beneficial effects:
[0020] 1) High selectivity: It can effectively separate natural organic matter and target pollutants, and achieve selective degradation of multi-component pollutants;
[0021] 2) Excellent catalytic performance: It exhibits excellent catalytic performance and high degradation efficiency during the PMS activation process;
[0022] 3) Good stability: The porous carbon outer shell and Co-N inner shell structure enhance the stability of the catalyst and prevent the aggregation and deactivation of active sites;
[0023] 4) Simple preparation method: Through the “layered temperature control, one-step carbonization” strategy, the preparation process is simple and easy for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the synthesis process of hollow multi-shell Co-N@C HoMS catalyst.
[0025] Figure 2 For ZIF-67@PDA( Figure 2 A) and Co-N@C HoMS( Figure 2 B) SEM image.
[0026] Figure 3 TEM image of Co-N@C HoMS.
[0027] Figure 4 Elemental mapping of Co-N@C HoMS.
[0028] Figure 5 XRD pattern of ZIF-67@PDA.
[0029] Figure 6 XRD pattern of Co-N@C HoMS.
[0030] Figure 7 This is the Co 2p XPS spectrum.
[0031] Figure 8 This is the N1s XPS spectrum.
[0032] Fig. 9 is the ratio of the hydrodynamic diameter to the actual particle size of Co-N@C HoMS.
[0033] Fig.10 Catalytic performance and characterization of the catalyst in the presence and absence of humic acid (HA): Fig.10 A) Degradation efficiency of carbamazepine (CBZ) in the presence and absence of HA in the system; ( Fig.10 B) The apparent rate constant (kobs) of CBZ degradation; Fig.10 C) Reaction conditions of TOC removal and Co ion leaching concentration in Co-N@C HoMS / HA system, where [PMS] = 0.12 g / L, [CBZ] = 5 mg / L, catalyst dosage = 0.1 g / L, [HA] = 10 ppm, initial pH 5.98, T = 25 °C.
[0034] Fig.11 Chemical composition analysis of Co-N@C HoMS after reaction: Co 2p ( Fig.11 A) and N1s XPS spectra ( Fig.11 B). DETAILED DESCRIPTION
[0035] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0036] The present invention provides a hollow multi-shell Co-N@C HoMS catalyst, which is synthesized from a ZIF-67 precursor through a "layered temperature control, one-step carbonization" strategy, and has a porous carbon outer shell and a Co-N inner shell structure. The porous carbon outer shell is a porous structure that can block large molecules (such as humic acid) from entering the interior; while the Co-N inner shell is rich in active sites and can efficiently catalyze the activation of peroxymonosulfate (PMS) to generate active oxygen species to degrade small molecular organic pollutants.
[0037] As a preferred embodiment of the present invention, the pore size of the porous carbon outer shell is 2-5 nanometers, and the thickness of the Co-N inner shell is 1-3 nanometers.
[0038] As a preferred embodiment of the present invention, the specific surface area of the catalyst is 300-500 m2 / g, and the pore volume is 0.5-1.0 cm3 / g.
[0039] The preparation method of the hollow multi-shell Co-N@C HoMS catalyst is as follows:
[0040] S1. Mix the ZIF-67 precursor with polydopamine (PDA) to form a ZIF-67@PDA complex.
[0041] As a preferred embodiment of the present invention, in this step, the mixing mass ratio of the ZIF-67 precursor to polydopamine is 1:(0.3-0.5), and the two are uniformly mixed at room temperature.
[0042] As a preferred embodiment of the present invention, in this step, the preparation method of the ZIF-67 precursor is as follows:
[0043] 7.50 mmol of Co(NO 3 ) 2 6H 2 0 and 32.3 mmol of 2-methylimidazole are dissolved in methanol and ethanol respectively, and after mixing, they are allowed to stand at room temperature (e.g., for 24 hours) to fully react to obtain a ZIF-67 precursor. In actual use, there is no special requirement for the amount of methanol and ethanol, as long as they can dissolve the corresponding solutes.
[0044] S2. The ZIF-67@PDA complex was heated from room temperature to 425°C at a heating rate of 0.6°C / min under a nitrogen atmosphere, kept warm for 1 hour, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain a hollow multi-shell Co-N@CHoMS catalyst.
[0045] The "layered temperature control, one-step carbonization" strategy of the present invention refers to raising the temperature twice respectively, and carbonization of the material is achieved through the two temperature increases.
[0046] The hollow multi-shell Co-N@C HoMS catalyst of the present invention is used to activate peroxymonosulfate (PMS) to degrade small molecular organic pollutants (such as carbamazepine) in water. In the presence of PMS, the Co-N@C HoMS catalyst can effectively separate macromolecules such as humic acid, so that small molecular organic pollutants such as carbamazepine are fully contacted with the active sites of the catalyst, thereby achieving efficient degradation.
[0047] As a preferred embodiment of the present invention, the organic pollutants include bisphenol A, phenol, p-chloroaniline, etc. in addition to carbamazepine. The water bodies that can be treated by the catalyst include domestic sewage, industrial wastewater and surface water.
[0048] As a preferred embodiment of the present invention, in actual use, the amount of the catalyst is 0.1-0.2 g / L, and the amount of the peroxymonosulfate is 0.1-0.3 g / L.
[0049] The method and effects of the present invention will be specifically described below through examples.
[0050] Example 1
[0051] In this example, a hollow multi-shell Co-N@C HoMS catalyst was prepared. Figure 1 As shown, the specific steps are as follows:
[0052] 7.50 mmol of Co(NO 3 ) 2 6H 2 O and 32.3 mmol of 2-methylimidazole were dissolved in methanol and ethanol, respectively, mixed and allowed to stand at room temperature for 24 hours to obtain ZIF-67. 200 mg of ZIF-67 was mixed with 60 mg of PDA and stirred at room temperature for 12 hours to obtain ZIF-67@PDA. ZIF-67@PDA was heated from room temperature to 425°C at a heating rate of 0.6°C / min under a nitrogen atmosphere, kept warm for 1 hour, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain a hollow multi-shell Co-N@C HoMS catalyst.
[0053] like Figure 2 and 3 As shown in the figure, the SEM and TEM images of the hollow multi-shell Co-N@C HoMS catalyst prepared by the present invention are shown. It can be seen from the figure that there are clear cavities between the layers, and the Co and N elements are evenly distributed in the inner shell layer, and the C element forms a complete carbon shell in the outermost layer. The details are as follows:
[0054] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the structural characteristics and surface morphology of Co-N@C HoMS. Figure 2 As shown in A, the synthesized ZIF-67@PDA has uniform size (700-800 nm) and a regular dodecahedral shape. The surface of ZIF-67@PDA is slightly rough due to the formation of a polydopamine coating on the surface of ZIF-67. ZIF-67@PDA exhibits good dispersibility, which is conducive to the subsequent formation of a hollow multi-shell structure. Figure 2 As shown in Figure B, the calcined Co-N@C HoMS (550–650 nm) maintained good dispersion and uniform dodecahedral shape, although the size was slightly smaller than that of the original ZIF-67 and ZIF-67@PDA. Figure 3 As shown in the transmission electron microscopy image, the overall morphology of the nanoparticles remains unchanged after calcination, but the dodecahedral structure is deformed and surface concave. Co-N@CHoMS has three shells. The outermost carbon shell is formed by carbonizing polydopamine and wrapping it on the surface of ZIF-67, which is tightly combined with the inner shell. The formation process of Co-N@C HoMS can be understood as follows: when ZIF-67@PDA is heated from room temperature to 425°C at a heating rate of 0.6°C / min, the slow heating rate causes ZIF-67 to gradually shrink and form a rigid outer shell, which continues to shrink, causing the outer shell to separate from the inner core to form the next shell. In addition, polydopamine rapidly decomposes at relatively low temperatures (250-550°C) and forms a hard outer carbon shell, thereby forming Co-N@C HoMS, whose interlayer cavities are clearly visible, as shown in Figure 2. Figure 2 and 3 shown.
[0055] Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) element distribution map ( Figure 4 ) showed that the Co and N elements were uniformly distributed in the inner shell, while the C element formed a complete carbon shell in the outermost layer. These results confirmed that the Co-N@C HoMS has a uniform inner Co-N double layer and an outer C shell, which enhances its efficiency and stability under complex reaction conditions. The cavity between the inner and outer shells reduces the mass transfer resistance and accelerates the effective contact between reactants, active sites, and reactive oxygen species.
[0056] Figure 5The results show that the XRD pattern of the synthesized ZIF-67 is consistent with the standard card of ZIF-67 (CCDC671073). The XRD spectrum of ZIF-67@PDA is not significantly different from that of the original ZIF-67, but the signal intensity is reduced, which indicates that the polydopamine (PDA) shell is amorphous, while the internal ZIF-67 structure maintains its crystallinity. The XRD diffraction peaks of the calcined Co-N@C HoMS lack the characteristic peaks associated with ZIF-67 ( Figure 6 ). The diffraction peaks at approximately 44.3° and 51.3° correspond to the (111) and (200) crystal planes of cobalt nanoparticles, respectively, indicating that the Co ions in the ZIF-67 structure were reduced to cobalt particles during calcination. The broad nature of the cobalt diffraction peaks indicates the presence of smaller cobalt nanoparticles in the sample, which generally expose more active sites, thereby enhancing catalytic activity. The diffraction angle at approximately 25° indicates typical graphitic carbon planes, indicating that the ZIF-67@PDA structure was transformed into a carbon framework under high-temperature carbonization. The study shows that cobalt nanoparticles promote the graphitization of amorphous carbon at high temperatures.
[0057] XPS was used to study the composition and valence state of Co-N@C HoMS. High-resolution Co2p spectra are shown in Figure 2. Figure 7 The figure shows a peak at 780.2 eV, which can be attributed to Co 0 The characteristic peak of the CoO phase was observed at 783.1 eV, although it was not detected in the XRD pattern, indicating that there was a small amount of oxidation on the surface of the cobalt nanoparticles. Figure 8 As shown in Figure 1, for the N1s high-resolution spectrum, three peaks were fitted at 400.9 eV, 399.8 eV, and 398.4 eV by curve fitting, corresponding to graphitic nitrogen, pyrrolic nitrogen, and pyridinic nitrogen, respectively. The proportion of graphitic nitrogen is lower than that of pyrrolic nitrogen and pyridinic nitrogen, which may be due to the lower calcination temperature.
[0058] The hydrodynamic diameters of Co-N HoMS and Co-N@C HoMS were measured by dynamic light scattering. The ratio of the hydrodynamic diameter to the actual particle size reflects the degree of aggregation. Fig. 9 As shown, the hydrodynamic diameter / true particle size ratio of Co-N@C HoMS is 0.586, indicating that Co-N@C HoMS has low aggregation degree and good stability in aqueous solution, which is beneficial for catalytic reactions.
[0059] Example 2
[0060] This example uses the hollow multi-shell Co-N@C HoMS catalyst prepared in Example 1 to verify the effect, as follows:
[0061] 5 mg of hollow multi-shell Co-N@CHoMS catalyst was added to 50 mL of 5 mg / L carbamazepine aqueous solution and ultrasonically dispersed for 1 minute. 0.3 mL of 100 mmol / L PMS aqueous solution was added to start the degradation reaction. Fig.10 A and Fig.10 As shown in B, within 10 minutes, the degradation rate of carbamazepine reached more than 99%, and the degradation rate was from 0.157min -1 Increased to 0.171min -1 . Even in the presence of 10 ppm humic acid, the degradation rate remained above 99%. In the presence of HA, Co-N@C HoMS exhibited a higher reaction rate, a phenomenon that confirms the selective degradation ability of Co-N@C HoMS, which may be due to the size exclusion effect of the outermost carbon shell, which prevents HA from shielding active sites or reacting with free radicals, thereby maintaining efficient pollutant degradation ability. Therefore, in the Co-N@C HoMS / HA / CBZ system (i.e., the system contains Co-N@C HoMS, HA, and CBZ), the shell-heterogeneous Co-N@C HoMS acts as an effective material that can intercept large molecules and allow small molecules to pass through, highlighting its importance in the selective removal of organic pollutants.
[0062] The concentration of Co ions dissolved during the reaction was determined by atomic absorption spectroscopy (AAS, PE AA800). 10 mL of the reaction solution was taken from the reaction solution every 10 minutes, filtered through a 0.22 μm PTFE injection filter microfiltration membrane into a centrifuge tube, and the Co ion concentration was determined. The results are shown in Figure 2. Fig.10 As shown in Figure C, after 10 minutes of reaction in the Co-N@C HoMS / PMS system, the dissolution concentration of cobalt ions was only 0.37 mg / L. The excellent CBZ degradation performance and low cobalt dissolution of Co-N@C HoMS are attributed to its heterogeneous hollow multi-shell structure, in which the outermost carbon shell isolates the HA that interferes with the degradation of pollutants through size screening, while the inner Co-N double layer provides abundant accessible active sites for catalytic reactions. In addition, the cavities between the shells help to increase the instantaneous concentration of the reactants, thereby facilitating the reaction. After testing in actual wastewater, the XRD spectrum and XPS full spectrum of Co-N@CHoMS after the catalytic reaction did not change significantly, as shown in Figure 3. Fig.11 This indicates that the catalyst has stability and potential for long-term use.
[0063] The catalyst of the present invention has a porous carbon outer shell and a Co-N inner shell structure. Its unique structural design enables it to effectively separate macromolecules (such as humic acid) and target pollutants (such as carbamazepine) in a complex water environment, achieving selective degradation of multi-component pollutants. The catalyst exhibits excellent catalytic performance and stability during the activation process of peroxymonosulfate (PMS), and has broad application prospects.
[0064] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A hollow multi-shell Co-N@C HoMS catalyst, characterized in that: It includes a porous carbon outer shell and a Co-N inner shell; the porous carbon outer shell is a porous structure used to block large molecules from entering the interior; the Co-N inner shell is rich in active sites and is used to catalyze the activation of peroxymonosulfate to generate active oxygen species to degrade organic pollutants.
2. The hollow multi-shell Co-N@C HoMS catalyst according to claim 1, characterized in that The pore size of the porous carbon shell is 2-5 nanometers.
3. The hollow multi-shell Co-N@C HoMS catalyst according to claim 1, characterized in that The thickness of the Co-N inner shell is 1-3 nanometers.
4. The hollow multi-shell Co-N@C HoMS catalyst according to claim 1, characterized in that The specific surface area of the catalyst is 300-500 m2 / g, and the pore volume is 0.5-1.0 cm3 / g.
5. A method for preparing a hollow multi-shell Co-N@C HoMS catalyst, characterized in that: The details are as follows: S1, mixing ZIF-67 precursor with polydopamine to form ZIF-67@PDA complex; S2. The ZIF-67@PDA composite was heated from room temperature to 425°C at a heating rate of 0.6°C / min under a nitrogen atmosphere, kept warm for 1 hour, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain a hollow multi-shell Co-N@C HoMS catalyst.
6. The method for preparing the hollow multi-shell Co-N@C HoMS catalyst according to claim 5, characterized in that: In S1, the mixing mass ratio of ZIF-67 precursor to polydopamine is 1:(0.3-0.5).
7. The method for preparing the hollow multi-shell Co-N@C HoMS catalyst according to claim 5, characterized in that: The preparation method of the ZIF-67 precursor is as follows: 7.50 mmol of Co(NO3)2·6H2O and 32.3 mmol of 2-methylimidazole were dissolved in methanol and ethanol, respectively, mixed, and allowed to stand at room temperature for sufficient reaction to obtain a ZIF-67 precursor.
8. A method for degrading organic pollutants in water, characterized in that: The details are as follows: In the presence of peroxymonosulfate, the hollow multi-shell Co-N@C HoMS catalyst obtained by the preparation method according to any one of claims 1 to 4 or any one of claims 5 to 7 is added to a water body, so that the porous carbon shell of the hollow multi-shell Co-N@C HoMS catalyst blocks the macromolecules in the water body from entering the interior, and the active sites of the Co-N inner shell catalyze the activation of peroxymonosulfate, and the generated active oxygen species fully contact with the small molecular organic pollutants in the water body to achieve the degradation of the small molecular organic pollutants.
9. The method for degrading organic pollutants in water according to claim 8, characterized in that: The organic pollutants include carbamazepine, bisphenol A, phenol and p-chloroaniline, and the water bodies include domestic sewage, industrial wastewater and surface water.
10. The method for degrading organic pollutants in water according to claim 8, characterized in that: The dosage of the catalyst is 0.1-0.2 g / L, and the dosage of the peroxymonosulfate is 0.1-0.3 g / L.
Citation Information
Cited By
ZIF-based catalytic ceramic membrane, preparation method and application of ZIF-based catalytic ceramic membrane in water treatment
CN120189950A